Targeted and effective photodynamic therapy for cancer using functionalized nanomaterials - Eun Ji Hong; Dae Gun Choi; Min Suk Shim (Elsevier, 2016)
Photodynamic therapy (PDT) is an emerging, non-invasive therapeutic strategy that involves photosensitizer (PS) drugs and external light for the treatment of diseases. Despite the great progress in PS-mediated PDT, their clinical applications are still hampered by poor water solubility and tissue/cell specificity of conventional PS drugs. Therefore, great efforts have been made towards the development of nanomaterials that can tackle fundamental challenges in conventional PS drug-mediated PDT for cancer treatment. This review highlights recent advances in the development of nano-platforms, in which various functionalized organic and inorganic nanomaterials are integrated with PS drugs, for significantly enhanced efficacy and tumor-selectivity of PDT.